2019
DOI: 10.3390/en12030365
|View full text |Cite
|
Sign up to set email alerts
|

Process Disturbances in Agricultural Biogas Production—Causes, Mechanisms and Effects on the Biogas Microbiome: A Review

Abstract: Disturbances of the anaerobic digestion process reduce the economic and environmental performance of biogas systems. A better understanding of the highly complex process is of crucial importance in order to avoid disturbances. This review defines process disturbances as significant changes in the functionality within the microbial community leading to unacceptable and severe decreases in biogas production and requiring an active counteraction to be overcome. The main types of process disturbances in agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 129 publications
(274 reference statements)
1
57
2
Order By: Relevance
“…Recent studies have reported the dominance of Bacteroidetes group under low-ammonium conditions, while under high concentrations the phylum Cloacimonetes disappears and the Firmicutes phylum, in particular Clostridiales and Lactobacillales orders, dominates the community (Werner et al, 2014;Vrieze et al, 2015;Regueiro et al, 2016;Westerholm et al, 2018). When high ammonia levels inhibit obligate acetoclastic methanogens, the microbial community shifts towards syntrophic acetate oxidation pathway (Westerholm et al, 2016) although the keystone taxa responsible for the function are unclear (Werner et al, 2014;Theuerl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the dominance of Bacteroidetes group under low-ammonium conditions, while under high concentrations the phylum Cloacimonetes disappears and the Firmicutes phylum, in particular Clostridiales and Lactobacillales orders, dominates the community (Werner et al, 2014;Vrieze et al, 2015;Regueiro et al, 2016;Westerholm et al, 2018). When high ammonia levels inhibit obligate acetoclastic methanogens, the microbial community shifts towards syntrophic acetate oxidation pathway (Westerholm et al, 2016) although the keystone taxa responsible for the function are unclear (Werner et al, 2014;Theuerl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion is a highly sensitive process exclusively carried out by microorganisms that are interdependently associated in a complex community and reside in a closed technical system with an environment controlled by the biogas plant operator [30]. Hence, it is crucial to understand how the biogas microbiomes respond to management measures and how this response affects the digestion process.…”
Section: Understanding the Digestion Processmentioning
confidence: 99%
“…In future biogas plants the microbial communities will be subjected to frequently varying process conditions while ensuring an overall stable digestion process with low susceptibility to disturbances. Process disturbances have manifold causes with different underlying mechanisms (e.g., unfavorable process temperature, fluctuating nutrient availability, overload of the degradation potential, accumulation of process inhibiting metabolites, and many others) [30]. Digester design and operation have to be aligned after the requirements of the microbiome in the sense of a microbial-based management [31], which is a precondition to improve stability and efficiency of the digestion process.…”
Section: Understanding the Digestion Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, plant operators will be forced to use a broad range of different feedstocks which are chemically very heterogeneous, variable over time, and often available only in small quantities. This will lead to a more inhomogeneous feedstock supply and sometimes to rapid feedstock changes, which might cause problems for the microbial community in the biogas reactors as the available nutrients and the bioaccesibility may differ [1,7].The production of biogas is a complex process where several different microorganisms using different metabolic pathways work together to degrade organic matter into biogas. The process can be divided into four main steps: the hydrolysis, the acidogenesis, the acetogenesis, and the methanogenesis.…”
mentioning
confidence: 99%